2017
DOI: 10.1016/j.nbd.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic neural entropy is a feature of freezing of gait in freely moving people with Parkinson's disease

Abstract: A novel turning and barrier course was superior to FW in eliciting FOG. Greater unpredictability in subthalamic beta rhythms was evident during stepping without freezing episodes in Freezers compared to Non-Freezers, whereas greater unpredictability in alpha rhythms was evident in Freezers during FOG. Non-linear analysis of dynamic neural signals during gait in freely moving people with PD may yield greater insight into the pathophysiology of FOG; whether the increases in STN entropy are causative or compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 75 publications
7
89
0
1
Order By: Relevance
“…This growing body of evidence supports the hypothesis that longer duration beta bursts in subcortical structures, equating to longer periods of beta oscillations and synchrony, represent pathological or impaired sensorimotor processing in Parkinson's disease (Anidi et al, 2018;Cagnan et al, 2019;Deffains et al, 2018;Lofredi et al, 2019b;Tinkhauser et al, 2018Tinkhauser et al, , 2017aTinkhauser et al, , 2017b and that one mechanism of STN DBS is to remove pathological sensorimotor network processing, while leaving intact normal physiological processing (Anidi et al, 2018;Holt et al, 2019;Tinkhauser et al, 2017a;Torrecillos et al, 2018). The discovery that averaged beta band power was attenuated during increasing intensities of DBS led to its successful use as the control variable in closed loop DBS studies Eusebio et al, 2011;Little et al, 2016aLittle et al, , 2016bLittle et al, , 2013Piña-Fuentes et al, 2019Rosa et al, 2017Rosa et al, , 2015Syrkin-Nikolau et al, 2017;Velisar et al, 2019;Whitmer et al, 2012). Similarly, the accumulating evidence suggests that beta burst duration will be a functionally relevant, patient specific control variable for closed loop DBS.…”
Section: Beta Burst Duration As a Biomarker Of The Efficacy Of Therapmentioning
confidence: 72%
See 1 more Smart Citation
“…This growing body of evidence supports the hypothesis that longer duration beta bursts in subcortical structures, equating to longer periods of beta oscillations and synchrony, represent pathological or impaired sensorimotor processing in Parkinson's disease (Anidi et al, 2018;Cagnan et al, 2019;Deffains et al, 2018;Lofredi et al, 2019b;Tinkhauser et al, 2018Tinkhauser et al, , 2017aTinkhauser et al, , 2017b and that one mechanism of STN DBS is to remove pathological sensorimotor network processing, while leaving intact normal physiological processing (Anidi et al, 2018;Holt et al, 2019;Tinkhauser et al, 2017a;Torrecillos et al, 2018). The discovery that averaged beta band power was attenuated during increasing intensities of DBS led to its successful use as the control variable in closed loop DBS studies Eusebio et al, 2011;Little et al, 2016aLittle et al, , 2016bLittle et al, , 2013Piña-Fuentes et al, 2019Rosa et al, 2017Rosa et al, , 2015Syrkin-Nikolau et al, 2017;Velisar et al, 2019;Whitmer et al, 2012). Similarly, the accumulating evidence suggests that beta burst duration will be a functionally relevant, patient specific control variable for closed loop DBS.…”
Section: Beta Burst Duration As a Biomarker Of The Efficacy Of Therapmentioning
confidence: 72%
“…The baseline was calculated from a frequency band within the same PD LFP spectrum, which overlapped and had similar burst dynamics to the simulated physiological 1/f spectrum. This baseline, from an 'inert' band in the same spectrum, can be used to determine burst durations and power in any other band in the spectrum and this allows comparison of burst dynamics across subjects, as commonly used for LFP power (Anidi et al, 2018;Syrkin-Nikolau et al, 2017). We demonstrate that the Anderson method captured a broader range of burst durations (with no power discrimination) in the pathological beta band compared to other power threshold methods.…”
Section: Introductionmentioning
confidence: 97%
“…[10][11][12] However, others found a correlation between STN-LFP recordings and tremor. 13,14 Furthermore, freezing-of-gait periods 15 and differentiation between speech and movement activities 16 can be detected using STN-LFPs. Such differentiation of clinical indications underlines the potential of STN-LFP recordings as promising input signals, with the added benefit of not requiring additional implants or equipment compared to cDBS.…”
Section: Adbs Based On Electrophysiological Recordings Basal Gangliamentioning
confidence: 99%
“…The room dividers were 6.5 feet high and a maximum of 3.75 inches wide. In the TBC, subjects walked around and through a narrow opening formed by room dividers (Syrkin-Nikolau et al, 2017), Figure 1A. The TBC was enclosed by a row of dividers on one side and a wall on the other, Fig.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The authors concluded that there is no "unique methodological tool that encompasses the entire complexity of FOG" and "further development of such an assessment tool requires understanding and thorough analysis of the specific FOG characteristics" (Barthel et al, 2016).Several studies have employed wearable inertial sensors in a variety of different tasks, such as turning 360 degrees in place for two minutes, walking around cones, or walking during dual tasking, to monitor, detect and predict FOG (Coste et al, 2014;Khemani et al, 2015;Kim et al, 2015;Kwon et al, 2014;Palmerini et al, 2017;Rezvanian and Lockhart, 2016;Silva de Lima et al, 2017;Zach et al, 2015). These tasks have improved the detection resolution of FOG but are either not representative of real-world environments or still require a clinical rater to detect freezing episodes, and cannot objectively measure gait impairment, such as arrhythmicity, that is correlated with FOG (Anidi et al, 2018;Hausdorff, 2009;Nantel et al, 2011;Plotnik and Hausdorff, 2008;Syrkin-Nikolau et al, 2017). An unmet need is a reliable, reproducible, objective measure of gait impairment and FOG using an easy to construct forward walking task, that mimics real-world environments that trigger FOG.…”
mentioning
confidence: 99%